Placental Transfer of Respiratory Syncytial Virus Antibody Among HIV-Exposed, Uninfected Infants. (24th September 2019) - Patel, Sweta M; Jallow, Sabelle; Boiditswe, Sefelani; Madhi, Shabir A; Feemster, Kristen A; Steenhoff, Andrew P; Arscott-Mills, Tonya; Muthoga, Charles; Ajibola, Gbolahan; Shapiro, Roger; Shah, Samir S; Cunningham, Coleen K; et al.
Abstract: Background: Maternal human immunodeficiency virus (HIV) infection is associated with lower placental transfer of antibodies specific to several childhood pathogens. Our objective for this study was to evaluate the effect of maternal HIV infection on the placental transfer of respiratory syncytial virus (RSV)-neutralizing antibodies. Methods: We conducted a cross-sectional study of mothers and their newborn infants at a tertiary hospital in Gaborone, Botswana, between March 2015 and December 2015. We measured serum RSV antibody levels by using a microneutralization assay. We used multivariable linear regression to evaluate the effect of maternal HIV infection on maternal RSV antibody levels, placental transfer of RSV antibodies, and newborn RSV antibody levels. Results: Of 316 mothers, 154 (49%) were infected with HIV. The placental transfer ratios for RSV antibodies to HIV-exposed, uninfected (HEU) and HIV-unexposed, uninfected infants were 1.02 and 1.15, respectively. The geometric mean titer (95% confidence interval) of RSV-neutralizing antibodies was 2657 (2251–3136) among HEU newborns and 2911 (2543–3331) among HIV-unexposed, uninfected newborns. In multivariable analyses, maternal HIV infection was associated with lower placental transfer of RSV antibodies ( P = .02) and a lower level of RSV antibodies among newborns ( P = .002). Among HEU newborns, higher birth weight ( P = .004) and an undetectable maternal antenatal viral load ( P = .01) were associated with more effective placental transfer of RSV antibodies. Conclusions: Maternal human immunodeficiency virus (HIV) infection is associated with lower mother-to-fetus transfer of serum RSV-neutralizing antibodies. HEU infants should be prioritized for preventive interventions for RSV. Maternal viral suppression through combination antiretroviral therapy has the potential to improve immunity to RSV among HIV-exposed infants. Abstract : Maternal HIV infection is associated with a lower rate of placental transfer of respiratory syncytial virus antibodies. Maternal viral suppression and higher newborn birth weight predicted more effective antibody transfer to HIV-exposed but uninfected newborns.